2018
DOI: 10.1182/bloodadvances.2017013599
|View full text |Cite
|
Sign up to set email alerts
|

Sipa1 deficiency–induced bone marrow niche alterations lead to the initiation of myeloproliferative neoplasm

Abstract: Key Points• Sipa1 loss leads to BM niche alterations prior to the initiation of MPN.• Sipa1-deficient BM niche induces lethal MPN from normal hematopoietic cells.Mutations of signal-induced proliferation-associated gene 1 (SIPA1), a RAP1 GTPaseactivating protein, were reported in patients with juvenile myelomonocytic leukemia, a childhood myelodysplastic/myeloproliferative neoplasm (MDS/MPN). Sipa1 deficiency in mice leads to the development of age-dependent MPN. However, Sipa1 expression in bone marrow (BM) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 61 publications
1
39
0
Order By: Relevance
“…Furthermore, Sipa1 reduction in AML MSCs and MPCs might contribute to AML progression, since Sipa1 loss could induce BM niche alterations, causing myeloproliferative neoplasms. 31 In summary, our findings provide new evidence for MLL-AF9 AML-induced dynamic niche alterations and the temporal roles of BM MSPCs during the development of AML. BM native Ebf2 1 cells suppress AML onset and progression.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Furthermore, Sipa1 reduction in AML MSCs and MPCs might contribute to AML progression, since Sipa1 loss could induce BM niche alterations, causing myeloproliferative neoplasms. 31 In summary, our findings provide new evidence for MLL-AF9 AML-induced dynamic niche alterations and the temporal roles of BM MSPCs during the development of AML. BM native Ebf2 1 cells suppress AML onset and progression.…”
Section: Discussionmentioning
confidence: 59%
“…and Runx2 remained unaltered, while the late-stage osteoblast marker Col1a1 and Bglap (osteocalcin) decreased in AML MSPCs, indicating a possible osteoblast maturation block in AML. Interestingly, Sipa1, whose expression in the BM niche is critical for maintaining normal hematopoiesis, 31 was significantly decreased in AML MSCs and MPCs ( Figure 4A-B).…”
Section: Dynamic Molecular Alteration Of Bm Cellular Niches In Aml Micementioning
confidence: 99%
“…Rap1 is a molecular switch of the Ras family that regulates cell signaling through diverse cellular receptors; it is activated to a GTP form by specific GEF linked to various receptors, whereas it is swiftly inactivated to a GDP form by GAP, represented by C3G and Sipa1, respectively . Although C3G is expressed rather ubiquitously in many tissues, Sipa1 is predominantly expressed in hematopoietic tissues, including both hematopoietic cells and stroma cells . We previously reported that Sipa1‐ deficient mice develop quite diverse late‐onset hematopoietic disorders, ranging from pancytopenia resembling MDS to overt MPN .…”
Section: Introductionmentioning
confidence: 99%
“…17 As wild-type BMC also developed MDS/MPN of late onset in Sipa1 −/− recipients, the overall effects in Sipa1-deficiency were, in part, attributed to dysregulated niche cell function. 15 Thus, involvement of Rap1 signaling in regulating HSPC per se remains to be verified.…”
mentioning
confidence: 99%
See 1 more Smart Citation